Effect of J3 perturbation on satellite position in LEO. Issue 1 (2nd January 2018) - Qi, Nai-ming; Sun, Qilong; Yang, Yong
Abstract : Purpose: The purpose of this paper is to study the effect of J3 perturbation of the Earth's oblateness on satellite orbit compared with J2 perturbation. Design/methodology/approach: Based on the parametric variation method in the time domain, considering more accurate Earth potential function by considering J3 -perturbation effect, the perturbation equations about satellite's six orbital elements (including semi-major axis, orbit inclination, right ascension of the ascending node, true anomaly, eccentricity and argument of perigee) has been deduced theoretically. The disturbance effects of J2 and J3 perturbations on the satellite orbit with different orbit inclinations have been studied numerically. Findings: With the inclination increasing, the maximum of the semi-major axis increases weakly. The difference of inclination disturbed by the J2 and J3 perturbation is relative to orbit inclinations. J3 perturbation has weak effect on the right ascension and argument of perigee. The critical angle of the right ascension and argument of perigee which decides the precession direction is 90° and 63.43°, respectively. The disturbance effects of J2 and J3 perturbations on the argument of perigee, right ascension and eccentricity are weakened when the eccentricity increases, simultaneously, the difference of J2 and J3 perturbations on argument of perigee, right ascension and argument of perigee decreases with eccentricity increasing, respectively. Practical implications: In the future, satellites need to orbit the Earth much more precisely for a long period. The J3 perturbation effect and the weight compared to J2 perturbation in LEO can provide a theoretical reference for researchers who want to improve the control accuracy of satellite. On the other hand, the theoretical analysis and simulation results can help people to design the satellite orbit to avoid or diminish the disturbance effect of the Earth's oblateness. Originality/value: The J3 perturbation equations of satellite orbit elements are deduced theoretically by using parametric variation method in this paper. Additionally, the comparison studies of J2 perturbation and J3 perturbation of the Earth's oblateness on the satellite orbit with different initial conditions are presented.